Genome-wide analysis of NDR1/HIN1-like genes in pepper (Capsicum annuum L.) and functional characterization of CaNHL4 under biotic and abiotic stresses. (1st June 2020) - Liu, Changyun; Peng, Haoran; Li, Xinyu; Liu, Chaolong; Lv, Xing; Wei, Xuefeng; Zou, Aihong; Zhang, Jian; Fan, Guangjin; Ma, Guanhua; Ma, Lisong; Sun, Xianchao
Abstract: Plant NDR1/HIN1-like ( NHL ) genes play an important role in triggering plant defenses in response to biotic stresses. In this study, we performed a genome-wide identification of the NHL genes in pepper ( Capsicum annuum L.) and characterized the functional roles of these CaNHL genes in response to abiotic stresses and infection by different pathogens. Phylogenetic analysis revealed that CaNHL s can be classified into five distinct subgroups, with each group containing generic and specific motifs. Regulatory element analysis showed that the majority of the promoter regions of the identified CaNHL s contain jasmonic acid (JA)-responsive and salicylic acid (SA)-responsive elements, and transcriptomic analysis revealed that CaNHL genes are expressed in all the examined tissues of pepper. The CaNHL1, CaNHL4, CaNHL6, CaNHL10, CaNHL11, and CaNHL12 genes were significantly upregulated under abiotic stress as well as in response to different pathogens, such as TMV, Phytophthora capsici and Pseudomonas syringae . In addition, we found that CaNHL4 localizes to the plasma membrane. CaNHL4 -silenced pepper plants display significantly increased susceptibility to TMV, Phytophthora capsici and Pseudomonas syringae, exhibiting reduced expression of JA-related and SA-related genes and reduced ROS production. However, transient overexpression of CaNHL4 in pepper increases the expression of JA-related and SA-related genes, enhances the accumulation of ROS, and inhibits the infection of these three pathogens. Collectively, for the first time, we identified the NHL genes in pepper and demonstrated that CaNHL4 is involved in the production of ROS and that it also regulates the expression of JA-related and SA-related genes in response to different pathogens, suggesting that members of the CaNHL family play an essential role in the disease resistance of pepper.